Process evaluation of a medical student-delivered smoking prevention program for secondary schools: protocol for the education against tobacco cluster randomized trial - Brinker, Titus Josef; Buslaff, Fabian; Suhre, Janina Leonie; Hillebrand, Gabriel; Mons, Ute; Haney, Ailís Ceara; Haney, Caelán Max; Schaible, Samuel; Tran, Dinh Thien-An; Srivastava, Aayushi; Enk, Alexander; Fröhling, Stefan; et al. (JMIR Research Protocols)
Background: Most smokers start smoking during their early adolescence under the impression that smoking entails positive attributes. Given the addictive nature of cigarettes, however, many of them might end up as long-term smokers and suffering from tobacco-related diseases. To prevent tobacco use among adolescents, the large international medical students’ network Education Against Tobacco (EAT) educates more than 40,000 secondary school students per year in the classroom setting, using evidence-based self-developed apps and strategies. Objective: This study aimed to evaluate the long-term effectiveness of the school-based EAT intervention in reducing smoking prevalence among seventh-grade students in Germany. Additionally, we aimed to improve the intervention by drawing conclusions from our process evaluation. Methods: We conduct a cluster-randomized controlled trial with measurements at baseline and 9, 16, and 24 months postintervention via paper-and-pencil questionnaires administered by teachers. The study groups consist of randomized schools receiving the 2016 EAT curriculum and control schools with comparable baseline data (no intervention). The primary outcome is the difference of change in smoking prevalence between the intervention and control groups at the 24-month follow-up. Secondary outcomes are between-group differences of changes in smoking-related attitudes and the number of new smokers, quitters, and never-smokers. Results: A total of 11,268 students of both sexes, with an average age of 12.32 years, in seventh grade of 144 secondary schools in Germany were included at baseline. The prevalence of cigarette smoking in our sample was 2.6%. The process evaluation surveys were filled out by 324 medical student volunteers, 63 medical student supervisors, 4896 students, and 141 teachers. Conclusions: The EAT cluster randomized trial is the largest school-based tobacco-prevention study in Germany conducted to date. Its results will provide important insights with regards to the effectiveness of medical student-delivered smoking prevention programs at school. International Registered Report Identifier (IRRID): DERR1-10.2196/13508 [JMIR Res Protoc 2019;8(4):e13508]
Gesehen am 14.04.2020